Things left unsaid [large type] - Walsh, Courtney, 1975- (Center Point Large Print, 2019)
"Lyndie St. James returns to her childhood summer home of Sweethaven for her best friend's wedding. The tragic death of their childhood friend Cassie has haunted them for ten years, as well as Cassie's family. Now reunited, each of them has a choice: to reveal the truths of that night or continue to live in its shadow"--